Validation of a Trauma Questionnaire in Veteran Women - McIntyre, Lauren M (Blackwell Science Inc, 1999)
The Trauma Questionnaire (TQ) assesses a woman’s history of childhood and adult sexual trauma, sexual harassment, and domestic violence. The TQ is used widely at Veterans Affairs Medical Centers, but its validity has not been thoroughly examined. In a prospective study of 127 women, we found the TQ to have good to excellent agreement with a semistructured clinician interview and good sensitivity and specificity. The TQ can be used as a valid alternative to the clinician interview in the initial elicitation of trauma history among women veterans in the primary care setting.